A Study On Service Quality Dimensions And Service Gap In Information Technology With Respect To Customer Loyalty In Banking (International Journal of Food and Nutritional Sciences, 2022)
Purpose: The purpose of this study is to analyze service quality dimension and service gap.Theoretical framework: Uncertainty reduction theory is used for understanding the concept of service dimension.Design/methodology –The primary quantitative method along with survey process is sued in the study. Approach: Graphical analysis and statistical interpretation has been executed. Findings: The implications of customer services are crucial to support customer loyalty in the banking industry.Research, practical and social implications: The study offers critical analysis on the research topic of customer service quality dimension. Originality/value: The value of the study is depended on five major dimensions of the service qualities offered by banking sectors.